Urban-Rural Disparities in Bronchial Asthma: A Review of Environmental Determinants and Epidemiological Insights - Cecuła, Wiktoria; Ciechomski, Kamil; Rypel-Bośka, Joanna; Siuta , Natalia; Siuda, Elżbieta; Stupecka, Aleksandra; Migiel, Marcin; Brynczka, Izabela; Goleniewska, Klaudia; Miaśnikiewicz, Jakub (Quality in Sport, 2026)
Introduction and aim of the study. Bronchial asthma, as defined by the Global Initiative for Asthma (GINA, 2024), is a heterogeneous disease characterized by chronic inflammation of the airways. This study aims to investigate the impact of environmental factors, including air quality and early-life exposure to microbiota, on the prevalence and development of asthma in urban and rural populations. Brief overview of the current state of knowledge. Asthma currently affects approximately 300 million people worldwide, with its prevalence increasing, especially in industrialized countries. Exposure of children to diverse microbiota, typical of farming environments, is associated with a lower risk of developing asthma and atopic diseases, which supports the hygiene hypothesis. In contrast, air pollution in urban agglomerations-especially particulate matter (PM2.5, PM10), nitrogen oxides, and polycyclic aromatic hydrocarbons-represents a significant risk factor. The pathomechanism of asthma involves complex immune responses in which chronic inflammation and bronchial hyperresponsiveness are modulated by environmental factors. Epidemiological studies indicate a higher prevalence of asthma in cities, which is associated with reduced immune stimulation by diverse microflora and increased exposure to pollutants. Conclusion. Available data confirm the complex role of environmental factors in the etiology of asthma. Preventive strategies should include reducing air pollution, especially in urban areas, and promoting safe contact of children with natural microbiota. Further research integrating epidemiology, immunology, and environmental protection is essential to develop effective strategies for asthma prevention and treatment.